When Everything Beyond the Walls Is Wild : Being a Woman Outdoors in America - Guignard, Lilace Mellin (Book collections on Project MUSE., 2019)
In When Everything Beyond the Walls Is Wild, Lilace Mellin Guignard draws from emblematic moments and relationships in her own life to explore issues of gender, recreation, and environmental conservation. Born into a suburban family, Guignard wanted to get up close and personal with iconic American landscapes, but social pressures and cautionary tales told her that these spaces were not meant for her as a woman. Reflecting on the ways our culture socializes women to remain indoors, Guignard shares her own struggles with finding her place outdoors. Refusing to stay indoors and "safe," Guignard drove cross-country with her dog, worked as a river guide, and set out to climb Mount Whitney. She recounts navigating outdoor interactions with male friends and strangers that range from wonderful to awkward to frightening. Now that she is settled with her own family, Guignard writes about how it is still more difficult for women than men to prioritize outdoor recreation time. These stories expose how cultural messages about women shape their experiences and interactions when backpacking, paddling, rock climbing, and bicycling. They broaden readers'notions of what adventure is, what places are considered wild and worth our care, and what types of people enjoy the outdoors. Drawing upon the art of the memoir--and informed by analysis from women's studies and ecological literature--Guignard makes an impassioned case for why women and marginalized members of society should have the opportunity to experience nature. The self-reliance and connection with the natural world that outdoor recreation fosters are qualities we all need in order to do the work required by the environmental challenges ahead.--Provided by publisher.